Use of α-Lactalbumin and Caseinoglycomacropeptide as Biopeptide Precursors and as Functional Additives in Milk Beverages Fermented by L. helveticus - Katarzyna Skrzypczak; Emilia Fornal; Dorota Domagała; Waldemar Gustaw; Ewa Jabłońska-Ryś; Aneta Sławińska; Wojciech Radzki; Anna Kononiuk; Adam Waśko (International Journal of Food Science)
The objective of this investigation was to verify whether biologically active peptides (BAPs) could be obtained from water solutions of α-lactalbumin (α-la) and caseinoglycomacropeptide (CGMP) through an application of the new Lactobacillus helveticus strains. Also, the aim of this research was to determine the influence of addition of the analyzed protein preparations to milk subjected to fermentation by tested bacterial strains on the physicochemical properties of obtained milk beverages. The results indicate that CGMP is a more preferable source for the production of BAPs by the test bacteria than α-la. The antihypertensive and ACE inhibitory effects were the most widespread bioactivities among the detected BAPs. α-la containing fermented milk beverages had higher values of springiness, gumminess, chewiness, and resilience than analogous products containing CGMP, while CGMP-supplemented fermented products exhibited higher values of the hardness parameter. The highest values of hardness (0.416±0.05 N) were recorded for beverages fermented by DSMZ containing the addition of CGMP, while the lowest value of this parameter (0.186±0.06 N) was noted for products containing α-la and fermented by B734. Moreover, CGMP-containing fermented products were characterized by a generally higher value of the proteolysis index (PI) than analogous variants containing α-la. The use of analyzed strains and the selected protein preparations has a positive effect on the texture of fermented milk beverages and might contribute to an increase in the health-promoting potential of such products.